2013
DOI: 10.1128/aac.00423-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence of pOZ176, a 500-Kilobase IncP-2 Plasmid Encoding IMP-9-Mediated Carbapenem Resistance, from Outbreak Isolate Pseudomonas aeruginosa 96

Abstract: Pseudomonas aeruginosa 96 (PA96) was isolated during a multicenter surveillance study in Guangzhou, China, in 2000. Wholegenome sequencing of this outbreak strain facilitated analysis of its IncP-2 carbapenem-resistant plasmid, pOZ176. The plasmid had a length of 500,839 bp and an average percent G؉C content of 57%. Of the 618 predicted open reading frames, 65% encode hypothetical proteins. The pOZ176 backbone is not closely related to any plasmids thus far sequenced, but some similarity to pQBR103 of Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 56 publications
2
80
0
Order By: Relevance
“…Second, the activity profiles of the enzymes against a range of ␤-lactams allow for an interesting hypothesis: that the original enzyme IMP-1 that appeared in the early 1990s was a broad-spectrum enzyme that efficiently inactivated all older ␤-lactam antibiotics, i.e., penicillins, the first-generation cephalosporin cephalothin, the neutral third-generation cephalosporin cefotaxime, the cephamycin cefoxitin, and, moderately, the early carbapenem imipenem (hence its name imipenemase). Over time, possibly selected by exposure to newer ␤-lactams, variants with mutations at position 67 appeared, including IMP-9 with I67 in 2000 (57) and IMP-10 with F67, isolated from different strains from 1997 to 2000 (19). Both residues increased resistance to imipenem, the charged third-generation cephalosporin ceftazidime, and, especially for F67, the more recently introduced carbapenems meropenem and doripenem, which were FDA approved in 1996 and 2007, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the activity profiles of the enzymes against a range of ␤-lactams allow for an interesting hypothesis: that the original enzyme IMP-1 that appeared in the early 1990s was a broad-spectrum enzyme that efficiently inactivated all older ␤-lactam antibiotics, i.e., penicillins, the first-generation cephalosporin cephalothin, the neutral third-generation cephalosporin cefotaxime, the cephamycin cefoxitin, and, moderately, the early carbapenem imipenem (hence its name imipenemase). Over time, possibly selected by exposure to newer ␤-lactams, variants with mutations at position 67 appeared, including IMP-9 with I67 in 2000 (57) and IMP-10 with F67, isolated from different strains from 1997 to 2000 (19). Both residues increased resistance to imipenem, the charged third-generation cephalosporin ceftazidime, and, especially for F67, the more recently introduced carbapenems meropenem and doripenem, which were FDA approved in 1996 and 2007, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1), was 93% identical to that in an IMP-9-producing P. aeruginosa PA96 plasmid pOZ176 (accession no. KC543497; nt 409845 to 414689), which was isolated in 2000 in China (39).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Further analysis of the flanking regions revealed that it was very similar to the Tn6217 region in the bla IMP-9 -carrying plasmid pOZ176 from a clinical P. aeruginosa isolate from Guangzhou, China (20). The upstream and downstream regions of bla VIM-48 contained the aacA4-intI1-Tn1403-like and sul1-hp-IS6100 gene clusters, respectively.…”
mentioning
confidence: 99%